Behind closed doors: The role of debriefing and feedback in a professional rugby team - Middlemas, S. G.; Croft, H. G.; Watson, F. (International Journal of Sports Science & Coaching, 2018)
Despite the popularity of performance analysis with high performance rugby environments, limited attention has been paid to understanding how coaches and practitioners use this information to impact on performance. The aim of this case study was to gain an in-depth understanding of how a professional rugby team - playing in New Zealand`s ITM cup competition - uses the post-match and pre-match meetings to debrief after performance and preview prior to future performance. Multiple ethnographic techniques were employed to generate a comprehensive picture of the phenomena, including participant observation, video recordings, formal and informal interviews, field notes, descriptive statistics and document analysis. Each meeting was transcribed separately and analysed using an inductive content analysis process and themes were identified. The case study explores how four key factors - the role of the coach-facilitator, player engagement, leadership and the balance between reflection and preparation - impact on the debrief/preview process. The findings reveal that while considerable emphasis was placed on the importance of player learning and engagement in team meetings, delivery was often ad hoc, coach-driven and results-focused. ABSTRACT FROM AUTHOR